Impact Of Quality Product And Quality Service Of Customer Satisfaction At Vinz Ice Cream Cafe in Samarinda City - Mega Meiliyana Kusuma; Kadori Haidar; Vitria Puri Rahayu (Educational Studies: Conference Series, 2021)
This study aims to determine the effect of product quality and service quality on consumer satisfaction at Café Vinz Ice Cream in Samarinda City and to determine the level of significance of the influence of product quality and service quality on consumer satisfaction at Café Vinz Ice Cream in Samarinda City. This type of research is correlational with a quantitative approach. The population of this study were all consumers of Café Vinz Ice Cream with a predetermined sample of 96 respondents at Café Vinz Ice Cream. The data analysis technique in this study used multiple regression analysis, and using data collection obtained by distributing questionnaires to 96 respondents and interviews with 5 Café Vinz Ice Cream in Samarinda city to find out the responses given regarding product quality, service quality and customer satisfaction. The results showed that the results of the t-test obtained tcount = 5.693 > ttable = 1.661 and a significant value of 0.000 <0.05 then there was a partial and significant effect between product quality on consumer satisfaction, then obtained the value of tcount = 3.824 > ttable = 1.661 and the value of significant 0.000 <0.05 then there is a partial and significant effect between service quality on customer satisfaction. Based on the results of the f test, fcount = 102.448 > ftable = 3.09 with a significance level of 0.000 <0.05, it can be concluded that product quality and service quality simultaneously have a significant effect on consumer satisfaction variables. The results of the analysis using the coefficient of determination obtained a value of 0.688, which means that product quality and service quality have an effect of 68.8% on consumer satisfaction.